Analisis Single Index Model dalam Membentuk Portofolio Optimal pada Saham Perusahaan Jakarta Islamic Index (JII) Periode 2016 - 2020 - Ira Valentina Silalahi; Nugraha Nugraha; Maya Sari; Harini Fajar Ningrum (Sains: Jurnal Manajemen dan Bisnis, 2022)
This study aims to determine the Jakarta Islamic Index (JII) stocks which are included in the optimal portfolio, the size of the composition of the shares in the optimal portfolio; as well as the optimal expected return and portfolio risk. The type of research used in this research is descriptive research with a quantitative approach. This study uses secondary data in the form of stock prices for the period 2016-2020. The data analysis method used is stock analysis with a single index model. The results showed that five stocks from 30 stock samples is included in the optimal portfolio. Following are the stocks that make up the optimal portfolio and their composition: INCO (29.91%), ADRO (29.60%), UNTR (16.25%), INDF (12.26%), and ICBP (11.98%). The formed portfolio will produce an expected portfolio return of 1.53% and a portfolio risk level of 1.23%.